Strategies in Translating Idiomatic Expressions Found in Dave Pelzer's Novel A Child Called 'IT' Into A Child Called 'IT' by Danan Priatmoko - Sugiarti, Lilik; Andini, Thathit (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2015)
Strategies in Translating Idiomatic Expressions Found in Dave Pelzer's Novel A Child Called 'IT' Into A Child Called 'IT' by Danan Priatmoko